A small molecule cryptotanshinone induces non-enzymatic NQO1-dependent necrosis in cancer cells through the JNK1/2/Iron/PARP/calcium pathway - Ying Hou; Bingling Zhong; Lin Zhao; Heng Wang; Yanyan Zhu; Xianzhe Wang; Haoyi Zheng; Jie Yu; Guokai Liu; Xin Wang; Jose M. Martin-Garcia; Xiuping Chen (Acta Pharmaceutica Sinica B)
Human NAD(P)H: quinone oxidoreductase 1 (NQO1) is a flavoenzyme expressed at high levels in multiple solid tumors, making it an attractive target for anticancer drugs. Bioactivatable drugs targeting NQO1, such as β-lapachone (β-lap), are currently in clinical trials for the treatment of cancer. β-Lap selectively kills NQO1-positive (NQO1+) cancer cells by inducing reactive oxygen species (ROS) via catalytic activation of NQO1. In this study, we demonstrated that cryptotanshinone (CTS), a naturally occurring compound, induces NQO1-dependent necrosis without affecting NQO1 activity. CTS selectively kills NQO1+ cancer cells by inducing NQO1-dependent necrosis. Interestingly, CTS directly binds to NQO1 but does not activate its catalytic activity. In addition, CTS enables activation of JNK1/2 and PARP, accumulation of iron and Ca2+, and depletion of ATP and NAD+. Furthermore, CTS selectively suppressed tumor growth in the NQO1+ xenograft models, which was reversed by NQO1 inhibitor and NQO1 shRNA. In conclusion, CTS induces NQO1-dependent necrosis via the JNK1/2/iron/PARP/NAD+/Ca2+ signaling pathway. This study demonstrates the non-enzymatic function of NQO1 in inducing cell death and provides new avenues for the design and development of NQO1-targeted anticancer drugs.